Características físicas do lenho em grupos fenológicos foliares de arbóreas de cerrado - Venancio, Natalia Cristina (Universidade Federal de São Carlos, 2016)
Leaf phenological groups of cerrado tree species show significant differences not only concerning the maintenance of foliage throughout the year but also about reproductive phenology as the peak and duration of flowering. In addition to the vegetative and reproductive phenology, deciduous (DE) semideciduous (SD) and evergreen (EV) cerrado trees have canopy architecture and the type of branching and leaf production significantly different. Therefore, the structure and functionality of wood probably show significant differences in these three groups (DE, SD, and EV). We aimed to determine the physical characteristics of wood and their relationships in aerial and underground parts of DE, SD, and EV tree species of cerrado vegetation. Internal (density, porosity, and water storage capacity) and external (crown height and root depth) physical traits of wood were determined in species distributed in DE, SD, and EV in two stages of development: adult and in the initial growth. By sections of the trunk at the transition between aerial and underground portions, we obtained results from bark and trunk in studied leaf phenological groups. There was a significant difference between DE and EV in a functional gradient where we found SD species. This group showed similar values to DE or EV species or even significantly different from both groups depending on the analyzed trait. Thus, the species distributed in leaf phenological groups also differed significantly in internal and external physical characteristics of wood in branches, in the transition from aerial to aboveground part and underground portion. These results indicated species grouped by leaf phenology have several other physical characteristics significantly different. Therefore, leaf phenological groups of cerrado trees are, in fact, functional groups. It has been successfully used to show that leaf phenology is just one attribute among many others traits distributed in the canopy, stem, and root assembling tree species of cerrado in at least three functional groups. Therefore, regardless the phylogenetic relatedness in each foliar phenological group these species belong to a functional group. Adults DE species growing under natural conditions are taller and have branches less dense and with more imbibition capacity than EV species. Conversely, in early years of growth DE were still taller with a deeper root system but with branches, stem and roots less dense than EV species. The inversion of wood internal traits between DE-EV demonstrated that the strategies for the acquisition and use of resources changed during tree development. It resulted in adult individuals significantly different and these changes probably depended on the biomass accumulated (size) in cerrado trees. The identification of these functional groups of trees is useful for more efficient management of protected areas or for recovering degraded areas of cerrado vegetation. The functional groups of cerrado trees could be identified not only by a list of attributes significantly different but by the reliance among these traits. These relationships built up a particular syndrome in each functional group. Syndromes originated through compromises among characteristics result in specific skills for acquisition, use and storage resources in every tree functional group. These skills result in similar survival strategies (reproduction, growth, and defense) and responses to environmental stresses in each of these functional groups of tree species of the cerrado vegetation.
Keywords: Cerrado; Plantas lenhosas; Woody plants; CIENCIAS BIOLOGICAS::ECOLOGIA